Effects of curcumin supplementation on vitamin D levels in women with premenstrual syndrome and dysmenorrhea: a randomized controlled study - Leyla Arabnezhad; Mahtab Mohammadifard; Ladan Rahmani; Zahra Majidi; Gordon A. Ferns; Afsane Bahrami (BMC, 2022)
Abstract Background Vitamin D has an established role in female reproduction. There is also evidence for an association between vitamin D levels and menstrual problems such as premenstrual syndrome (PMS) and dysmenorrhea. Curcumin, is a bioactive polyphenol constituent of turmeric, that can potentially interact with vitamin D receptors and its molecular targets. This study evaluated the effects of curcumin on vitamin D levels in young women with PMS and dysmenorrhea. Methods In this randomized, triple-blind, placebo-controlled trial, women with PMS and dysmenorrhea were divided randomly into experimental and control groups to receive one capsule (500 mg of curcuminoid+ 5 mg piperine, or placebo) daily, from approximately 7 days before until 3 days after menstruation for three consecutive menstrual cycles. Serum vitamin D levels, renal function, and liver enzymes were also measured before and after intervention. Results A total of 76 subjects (38 in each group) were recruited into the trial. Curcumin significantly increased the median (IQR) serum levels of vitamin D [from 12.8 ng/ml (7.0-24.6) to 16.2 ng/ml (6.4-28.8); P = 0.045], compared with placebo [from 18.6 ng/ml (2.2-26.8) to 21.3 ng/ml (5.2-27.1); P = 0.17]. Serum levels of aspartate aminotransferase and direct bilirubin were reduced by the end of trial in the curcumin group (p < 0.05), but did not change significantly in the control group (p > 0.05). Finally, no significant differences in levels of fasting blood glucose were detected between curcumin and placebo groups. Conclusion Curcumin supplementation in women with PMS and dysmenorrhea led to a significant improvement of vitamin D, liver function enzyme test, but did not affect blood glucose. Trial registration The trial was registered on Iranian Registry of Clinical Trials registry (Trial ID: IRCT20191112045424N1 on 23 January 2020; available at https://www.irct.ir ).